Food Irradiation: A Solution for the Conservation and Safety of Perishable Foods in Naval Environments by the Brazilian Navy - P. A. Celestino; Roberto Gazola Ortiz; D. Levy (Brazilian Journal of Radiation Sciences)
The article discusses the application of food irradiation as a solution for food preservation and safety in naval settings, focusing on the missions of the Brazilian Navy's submarines. Food irradiation, recognized in 37 countries, effectively eliminates parasites, fungi, and bacteria, extending the shelf life of foods without compromising their nutritional and sensory qualities. The research used an electronic questionnaire to assess the knowledge and acceptance of food irradiation among military and civilian personnel of the Navy. Results indicate that before receiving information, 54% of participants were unaware of the technology, and 28% had a negative view of nuclear energy. After exposure to informative materials, 82% of participants expressed willingness to consume irradiated foods, up from 54% previously. The study highlights the importance of education and scientific dissemination for the acceptance of the technology and suggests expanding the study to a larger sample within the Navy. The findings suggest the potential use of food irradiation in Navy ships and submarines, contributing to the health and well-being of crew members.